2020
DOI: 10.1111/jopr.13284
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Patient‐Reported Outcomes of Single Posterior Implant‐Supported Restorations Completed by Predoctoral Students: A Retrospective Study with Up to 10 Years of Follow Up

Abstract: Purpose To assess clinical outcomes of screw‐retained implant‐supported restorations as well as patient satisfaction and Oral Health‐related Quality of Life (OHQoL), when treatment is performed in an academic setting by supervised predoctoral students. Materials and methods Ninety patients (n = 129 restorations) consented to participate in the study. The mean follow‐up period was 4.2 years (range: 4 months to 10.6 years) after crown insertion. All patients filled out a modified Oral Health Impact Profile quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Based on these definitions, 80.2% restorations were deemed suc-cessful, whereas 70.3% restorations were complication-free throughout the follow-up period. A recent retrospective study on posterior metal-ceramic and full cast implant-supported restorations completed by predoctoral students reported a 74.4% success rate at 10 years, 17 which is consistent with the findings of the present study. In a study reporting on lithium-disilicate implant-supported restorations, De Angelis et al 16 reported an 89% complication-free rate.…”
Section: Discussionsupporting
confidence: 92%
“…Based on these definitions, 80.2% restorations were deemed suc-cessful, whereas 70.3% restorations were complication-free throughout the follow-up period. A recent retrospective study on posterior metal-ceramic and full cast implant-supported restorations completed by predoctoral students reported a 74.4% success rate at 10 years, 17 which is consistent with the findings of the present study. In a study reporting on lithium-disilicate implant-supported restorations, De Angelis et al 16 reported an 89% complication-free rate.…”
Section: Discussionsupporting
confidence: 92%